The essentials of computer organization and architecture - Null, Linda (Jones & Bartlett Learning : Burlington, 2024)
"The Essentials of Computer Organization and Architecture focuses on the function and design of the various components necessary to process information digitally. This title presents computing systems as a
Keywords: Computer Engineering